First North American 50 cc Total Artificial Heart Experience: Conversion from a 70 cc Total Artificial Heart. Issue 5 (September 2016) - Khalpey, Zain; Kazui, Toshinobu; Ferng, Alice S.; Connell, Alana; Tran, Phat L.; Meyer, Mark; Rawashdeh, Badi; Smith, Richard G.; Sweitzer, Nancy K.; Friedman, Mark; Lick, Scott; Slepian, Marvin J.; et al.
Abstract : The 70 cc total artificial heart (TAH) has been utilized as bridge to transplant (BTT) for biventricular failure. However, the utilization of 70 cc TAH has been limited to large patients for the low output from the pulmonary as well as systemic vein compression after chest closure. Therefore, the 50 cc TAH was developed by SynCardia (Tucson, AZ) to accommodate smaller chest cavity. We report the first TAH exchange from a 70 to 50 cc due to a fit difficulty. The patient failed to be closed with a 70 cc TAH, although the patient met the conventional 70 cc TAH fit criteria. We successfully closed the chest with a 50 cc TAH.